ANALISIS KEMAMPUAN BERNALAR KRITIS DAN PERCAYA DIRI PADA MATERI MAGNET KELAS V SD NEGERI BINANGUN - Dian Wijayanti; Siska Desy Fatmaryanti; Nur Ngazizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the critical reasoning ability and analyze the confidence of students of magnetic material in grade V of SD Negeri Binangun. The learning process carried out by the homeroom teacher of class V still has students who have difficulties in solving problems, when given a spark question, an answer grid must be included so that students can answer. According to the homeroom teacher of class V, sometimes there are students who are not able to respond to the subject matter. The method during the learning process must be accompanied by real examples. This can be seen when students still have difficulty accepting the learning information obtained, have difficulty in inferring from learning and are still embarrassed to express opinions when learning takes place. This study uses a descriptive method with a qualitative approach. The subject of this study is grade V students of SD Negeri Binangun with a total of 18 students with a sample of 4 students with a critical reasoning subject sample and 3 students with a confident subject sample, with data collection techniques in this study using observation, test, interview, and documentation methods. The results obtained from students' critical reasoning skills are different, namely in four categories, namely very proficient, proficient, developed, and starting to develop. Meanwhile, students' confidence skills also vary, which are categorized into very well developed, developing, starting to develop, and not yet developing. Positive relationship between critical reasoning skills and self-confidence. Students who have high confidence tend to be more active in critical thinking, asking questions, and finding solutions to given problems. On the other hand, students with low confidence tend to be hesitant in making decisions and less courageous to express their opinions, so their critical thinking skills have not developed properly.